Water regulates the residence time of Benzamidine in Trypsin - Narjes Ansari; Valerio Rizzi; Michele Parrinello (Nature Communications, 2022)
Water is an essential part of any biological system, yet many aspects of its role remain elusive. Here the authors show, in a paradigmatic ligand-protein system, that water modulates the ligand residence time in a complex and non-local way, with possible implications in drug design.